The Significance of Clopidogrel Low-Responsiveness on Stent Thrombosis and Cardiac Death Assessed by the Verifynow P(2)Y(12) Assay in Patients With Acute Coronary Syndrome Within 6 Months After Drug-Eluting Stent Implantation - Lee, Kyounghoon (The Korean Society of Cardiology, 2009)
BACKGROUND AND OBJECTIVES: Clopidogrel resistance or low-responsiveness may be associated with recurrent atherothrombotic events after drug-eluting stent (DES) implantation. We prospectively evaluated the association between clopidogrel resistance assessed by the Verifynow™ P(2)Y(12) assay (Accumetrics, San Diego, CA, USA) and stent thrombosis (ST) or cardiac death (CD) in patients with acute coronary syndrome (ACS) within 6 months after DES implantation. SUBJECTS AND METHODS: We enrolled 237 consecutive patients (160 males, 65.2±10.3 years) with ACS who received a DES implantation. The composite endpoint was defined to CD or ST by Academic Research Consortium definitions within 6 months post-implantation. Clopidogrel resistance was defined as <20% inhibition of the P(2)Y(12) receptor. RESULTS: Baseline demographic characteristics were similar between 142 normal individuals and 95 clopidogrel resistant patients. CD occurred in one case (0.7%) in the normal group and two cases (2.13%) in the resistant group (p=0.344). There was no episode of ST in the normal group and four episodes in the resistant group (4.2%, four definite ST) (p=0.035). Univariate logistic regression revealed an adjusted odds ratio (OR) for composite end point of CD or ST of 9.646 {95% confidence interval (CI) 1.139-81.679}, and multivariate logistic regression for composite end point revealed an OR of 12.074 (95% CI 1.205-120.992). CONCLUSION: Clopidogrel low-responsiveness assessed by the Verifynow™ P(2)Y(12) assay is an independent predictor of ST and composite end point of ST or CD in patients with ACS within 6 months after DES implantation.